Asuhan Kebidanan Pada Balita Dengan Gizi Kurang Di Desa Ranah UPT Puskesmas Air Tiris Tahun 2024 - Sofia, Norafni; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
The problem of malnutrition in toddlers is a condition where body weight is below the growth curve. There are still many growth problems with malnutrition and obesity. If this nutritional problem is not treated in the long term, it will cause wasting and stunting. The causes of malnutrition in toddlers are also influenced by socio-economic conditions, low maternal education, maternal employment, number of children, maternal knowledge and parenting patterns, and a poor environment. The aim of the research is to provide midwifery care to toddlers with malnutrition in Ranah Village UPT Air Tiris Health Center in 2024. This research is in the form of a case study with descriptive observational methods carried out in Ranah Village on 12-24 July 2024. Results case study research given to An. A, namely, 4 visits were carried out over 2 weeks. Midwifery care consists of providing counseling to mothers of toddlers regarding balanced diets for toddlers, the dangers of diarrhea for toddlers, the dangers of acute respiratory infections, toddlers with coughs and colds, dengue fever, and clean and healthy living behavior (PHBS). Providing additional food in the form of cassava flour pancakes and green bean porridge, teaching mothers how to make cassava flour pancakes, giving mothers vegetables, tofu, tempeh, eggs for toddlers, encouraging mothers to continue to provide balanced food, encouraging mothers to maintain diet and rest. Based on the malnutrition care provided to An. At the age of 3 years, it was found that the condition of malnourished toddlers was starting to return to normal. The conclusion is that the care provided was carried out well and produced positive results. It is hoped that this research can serve as a reference, add to discourse, and develop knowledge regarding midwifery care for toddlers with malnutrition